Proceedings of the 13th World Conference on Titanium : sponsored by Titanium Committee of the Structural Materials Division of the Minerals, Metals & Materials Society (TMS), held August 16-20, 2015, Manchester Grand Hyatt, San Diego, California, USA /: sponsored by Titanium Committee of the Structural Materials Division of the Minerals, Metals & Materials Society (TMS), held August 16-20, 2015, Manchester Grand Hyatt, San Diego, California, USA. (2016) - Unknown
No abstract available